Integrative Review for Patients With Bilateral Total Knee Replacement: A Call for Nursing Practice Guidelines. (July 2018) - Pietsch, Theresa; David, Jonathan; Vergara, Franz
Abstract : BACKGROUND: The aim of this joint project between the National Association of Orthopaedic Nurses and the Association of Rehabilitation Nurses was to develop nursing practice guidelines for patients who experience bilateral knee arthroplasty (BTKA) across the continuum of care. No guidelines existed and an integrative review was completed to address this gap. METHODS: An integrative review of refereed quantitative and qualitative research in published and gray literature was completed to answer the clinical questions: (1) What is the scope of evidence-based nursing interventions for patients undergoing BTKA? (2) What are patients' experiences with BTKA across the care continuum? The scope of the literature search was patients with bilateral and unilateral total knee arthroplasty. An evidence-based system was used to rate the strength of studies that met the criteria for inclusion in this review. RESULTS: The search method identified 588 potential titles but the analysis of the abstracts supported only 128 studies for possible inclusion in this project. The authors independently reviewed these studies and concluded that 126 studies did not meet the inclusion criteria and 2 quantitative studies were eligible for inclusion. CONCLUSIONS: Understanding which interventions are most effective for pain management, functional gains, quality of life, and other nurse-sensitive outcomes is best derived from empirical studies. Most likely, BTKA nursing care is being guided by clinical experts and not by empirical nursing evidence. In the absence of empirical evidence, it is feasible that nurses can extrapolate findings from other studies to guide and support the care of BTKA patients. Research recommendations include the exploration of early mobilization interventions, development of nursing care bundles, and evaluation of patient-centered outcomes at the points of transitional care.